2021
DOI: 10.3389/ffgc.2021.675475
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Natural Forests After Severe Wind Disturbance in a Cold, Snowy Region With a Deer Population: Implications From 15 Years of Field Experiments

Abstract: Questions have been raised about the application of conventional post-windthrow forest practices such as salvage logging, site preparation, and afforestation in response to the increase in wind disturbance caused by climate change. In particular, it is necessary to identify effective forest management practices that consider the pressure from deer browsing in forests in cold, snowy regions because the population of ungulates is expected to increase. The impacts of legacy destruction, i.e., the destruction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Morimoto et al. (2021) found that mean CWM height decreased significantly from 0.98 m to 0.38 m after 10 years, and Barker Plotkin et al. (2013) report a dramatic height reduction after 20 years (their Figure 4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Morimoto et al. (2021) found that mean CWM height decreased significantly from 0.98 m to 0.38 m after 10 years, and Barker Plotkin et al. (2013) report a dramatic height reduction after 20 years (their Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…‘jackstraws’) killed by fire can provide browsing refugia for aspen and willow regeneration (Ripple & Larsen, 2001). Large influxes of CWM from windstorms might serve a similar purpose; however, this potential exclosure effect remains poorly understood (but see Hagge et al., 2019; Konôpka et al., 2021; Morimoto et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A ground survey was also conducted on the same day. Because the high density of recovering juvenile trees [43] blocked the way, it was not possible to take samples of all fallen and snapped trees from the whole study area. The sample positions of fallen and snapped trees were taken in accessible areas using the RTK system, which corresponded…”
Section: Data Acquisitionmentioning
confidence: 99%
“…A ground survey was also conducted on the same day. Because the high density of recovering juvenile trees [43] blocked the way, it was not possible to take samples of all fallen and snapped trees from the whole study area. The sample positions of fallen and snapped trees were taken in accessible areas using the RTK system, which corresponded to around 78% of the total area (Appendix A, Figure A1); for each fallen tree, two GNSS coordinates were taken (one at each end of a fallen tree), and for each snapped tree, one GNSS coordinate was taken.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The cumulative volume of broken or felled trees was approximately 460,000 m 3 , of which 246,000 m 3 were mass windthrows, meaning that the entire forest area was affected. The biggest damages were recorded in Bihor (200,000 m 3 ), Arad (85,000 m 3 ), and Maramures , counties (70,000 m 3 ) [50]. In the Sudrigiu Forest District, managed by the Bihor Forest Directorate, which administers a total forest area of 2177.7 ha, the estimated timber losses exceeded 60,000 m 3 .…”
Section: Introductionmentioning
confidence: 98%